Exogenous dsRNA-Mediated RNAi: Mechanisms, Applications, Delivery Methods and Challenges in the Induction of Viral Disease Resistance in Plants - Emmadi Venu; Akurathi Ramya; Pedapudi Lokesh Babu; Bhukya Srinivas; Sathiyaseelan Kumar; Namburi Karunakar Reddy; Yeluru Mohan Babu; Anik Majumdar; Suryakant Manik (Viruses)
The increasing challenges posed by plant viral diseases demand innovative and sustainable management strategies to minimize agricultural losses. Exogenous double-stranded RNA (dsRNA)-mediated RNA interference (RNAi) represents a transformative approach to combat plant viral pathogens without the need for genetic transformation. This review explores the mechanisms underlying dsRNA-induced RNAi, highlighting its ability to silence specific viral genes through small interfering RNAs (siRNAs). Key advancements in dsRNA production, including cost-effective microbial synthesis and in vitro methods, are examined alongside delivery techniques such as spray-induced gene silencing (SIGS) and nanocarrier-based systems. Strategies for enhancing dsRNA stability, including the use of nanomaterials like layered double hydroxide nanosheets and carbon dots, are discussed to address environmental degradation challenges. Practical applications of this technology against various plant viruses and its potential to ensure food security are emphasized. The review also delves into regulatory considerations, risk assessments, and the challenges associated with off-target effects and pathogen resistance. By evaluating both opportunities and limitations, this review underscores the role of exogenous dsRNA as a sustainable solution for achieving viral disease resistance in plants.